PRAKTIK NEGARA-NEGARA ATAS KONSEPSI NEGARA KEPULAUAN - Agoes, Etty R. (Indonesian Journal of International Law, 2021)
Since the succesful adoption of archipelagic state principle in the UNCLOS that was basically sponsored by states whose territory mostly consists of island or group of islands surrounding by sea, there are only nineteen countries out of twenty-four countries that can be considered as archipelagic state, that have enacted their domestic regulations governing their policy toward their sea territory. It can be said further that Indonesia is the only one of nineteen countries who has its domestic regulation in purpose to honor the obligations under Convention on the Law of the Sea 1982 (UNCLOS) and to build strong relationship with international organizations. Based on those facts, it seems that the successful of adopting the regime archipelagic state in international law arena has not been well followed by the support of domestic regulations beacuse of some kind of barriers in each country. Indonesia has to be patient for waiting other countries to handle out their problems and then implement their obligations like Indonesia does.